Evaluation of Intraoperative Surgical Adjuncts and Resection of Glioblastoma (ELISAR GB): A UK and Ireland, multicentre, prospective observational cohort study. (15th October 2021) - Solomou, Georgios; Gharooni, Ali; Piper, Rory J; Kolias, Angelos G; Fountain, Daniel M; Ashkan, Keyoumars; Gough, Melissa; Khan, Danyal Z; Plaha, Puneet; Whitehouse, Kathrin; Jenkinson, Michael; Price, Stephen; et al.
Abstract: Aims: Extent of resection is associated with better survival in patients with glioblastoma. Numerous surgical adjuncts can be used to achieve maximal safe resection - including fluorescence-guidance with 5-aminolevulinic acid (5-ALA), neuronavigation, intraoperative ultrasound (IoUS), intra-operative MRI (iMRI), tractography, electrophysiological monitoring and awake surgery. We evaluated the availability, use and operative aim and success associated with these adjuncts. Method: This is a prospective cohort study of 27 of 31 neurosurgical centres in the UK and Ireland from 6 January to 19 March 2020. Consecutive cases were identified through neuro-oncology multidisciplinary meetings. Eligible cases included adults with a supratentorial histopathologically confirmed glioblastoma with pre/post-operative reported T1-weighted MRI with contrast deemed suitable for resection. Outcomes included the availability and usage of surgical adjuncts, and the percentage of operations that achieved their aim of complete resection, defined as complete resection of enhancing tumour (CRET) on post-operative T1-MRI. We present the initial descriptive statistics from this national study. Results: 232 patients with glioblastoma were included. In 142 patients (61.2%) the surgical aim was CRET. 5-ALA and neuronavigation were available in all centres (Figure 1). The most commonly used neurosurgical adjunct was neuronavigation (88.2%) (Figure 2). The proportion of patients receiving 5-ALA in CRET and debulking-only groups was 65.0% and 48.9%, respectively. 35 different combinations of adjuncts were found in total, with 13 unique combinations only used in one instance (Figures 1 & 2). CRET was achieved in 69/142 (45.8%) patients in which was the aim. 9/90 (10%) patients in the debulking-only group achieved CRET, of which 7/9 (77.8%) had received 5-ALA. Of the three most frequently used combination of adjuncts for patients deemed feasible for CRET, the most successful in terms of achieving CRET was the combined use of neuronavigation, 5-ALA and IoUS, with post-operative CRET at 47.4% (Figure 3). Conclusion: ELISAR-GB has collated prospective data to demonstrate the current use of intraoperative adjuncts in the UK and Ireland. There is marked heterogeneity with regards to combinations of adjuncts used. A CRET of 47% is lower than would be expected compared to previously published literature, possibly due to a more stringent definition of complete resection in this study. Based on these early descriptive results, there is no clear combination of adjuncts that shows superiority and use of 5-ALA does not always result in CRET when it is the surgical aim. Of interest, 5-ALA is being used for operations that do not aim for complete resection, a change in indication. The FUTURE GB trial will provide more conclusive evidence on the efficacy of surgical adjuncts to maximise extent of resection.